Elites moved toward democrats more than nonelites moved away: Income, education, and occupational class in US presidential elections, 1980–2020 - Karyn Vilbig; Paula England (Proceedings of the National Academy of Sciences, 2026)
Recent discussion of voting in US elections claims a strong movement of White working-class voters away from voting for Democrats, with much discussion focusing only on elections between 2012 and the present. We examine longer-term trends from 1980 to 2020 in how more and less privileged White voters—measured by household income, education, and occupational class—moved toward or away from voting Democratic. We also explore how these movements changed the shape of the relationships between these three socioeconomic indicators and voting Democratic. We find little evidence of a long-term movement away from Democrats among voters with lower income, less education, or working-class jobs, although there is some evidence of this after 2012. The clearest long-term trend is that voters in the highest decile of income, college graduates, and white-collar workers moved steadily toward voting Democratic across the 40 y. Thus, the change from negative to flat for income’s relationship to voting Democratic, and from negative to positive for education’s relationship to voting Democratic comes less from a movement of less privileged voters away from Democratic voting and more from a long-term movement of those in the top decile of income, college graduates, and white-collar workers toward voting Democratic. Whether the post-2012 movement away from voting Democratic among voters without a high school degree and in working-class jobs becomes an enduring trend or is idiosyncratic to Trump’s candidacy is an important question for future research.